Is there a Need for Proximity in the Urban Knowledge Economy? A Geostatistical Analysis of Research Cluster in Vienna - Musil, Robert; Eder, Jakob (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
Urbanization and the knowledge economy are two concepts which are interlinked and therefore agglomerations are nowadays often considered as the centres of innovation. However, the importance of local buzz, in other words the spontaneous exchange of actors, and the existence of a tacit knowledge, was questioned in more recent empirical studies. There are indications that the access to global pipelines might be more important. Based on the analysis of 1,363 research facilities in Vienna (using spatial-statistical methods), the spatial patterns of Vienna’s research sector (considering five sub-sectors) are determined and pronounced concentrations are found. In addition, expert interviews show that the relevance of local and/or international cooperation as well as the reasons which lead to “knowledge clusters” cannot be generalized. Spatial proximity is sometimes caused by historical locations and has different meanings for different research sectors. Hence, spatial proximity should not necessarily be seen as contradictory to the increasing importance of global pipelines, which is observed in recent studies. On the one hand, spatial proximity reduces risks, which are side effects of international cooperation. On the other hand, it is actually inevitable in some research sectors. This leads to the following conclusions: First, the innovation research should take sector specific tendencies for concentrations more into account. Second, urban policy makers are advised to consider in detail the specific needs of the actors in question. In doing so, it is more likely, that research and development policies will succeed.